2021
DOI: 10.1101/2021.07.24.21261040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel risk factors for Coronavirus disease-associated mucormycosis (CAM): a case control study during the outbreak in India

Abstract: Background: The epidemiology of the Coronavirus-disease associated mucormycosis (CAM) syndemic is poorly elucidated. We aimed to identify risk factors that may explain the burden of cases and help develop preventive strategies. Methods: We performed a case-control study comparing cases diagnosed with CAM and those who had recovered from COVID-19 without developing mucormycosis (controls). Information on comorbidities, glycemic control, and practices related to COVID-19 prevention and treatment was recorded. Re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Diabetes mellitus as a risk factor for ROCM is well documented during the pre-COVID era [ 5 , 25 ]. In COVID-19 pandemic, pre-existing diabetes could worsen glycaemic control, thereby causing ketoacidosis and increasing the risk of mucormycosis [ 26 , 27 ]. Our finding is consistent with published studies reporting a higher risk of mucormycosis among people with diabetes and more so after COVID-19 [ 4 , 9 , 11 , 24 , 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus as a risk factor for ROCM is well documented during the pre-COVID era [ 5 , 25 ]. In COVID-19 pandemic, pre-existing diabetes could worsen glycaemic control, thereby causing ketoacidosis and increasing the risk of mucormycosis [ 26 , 27 ]. Our finding is consistent with published studies reporting a higher risk of mucormycosis among people with diabetes and more so after COVID-19 [ 4 , 9 , 11 , 24 , 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes did not differ significantly between patients with different underlying host factors 23 . Patients with severe COVID‐19 are at an increased risk to develop secondary fungal infections with aspergillus or mucor 24–27 . A review showed the prevalence of COVID‐19 associated pulmonary aspergillosis (CAPA) to be around 8.6%.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Patients with severe COVID‐19 are at an increased risk to develop secondary fungal infections with aspergillus or mucor. 24 , 25 , 26 , 27 A review showed the prevalence of COVID‐19 associated pulmonary aspergillosis (CAPA) to be around 8.6%. Destruction of the bronchial mucosa and alveolar injury, COVID‐19 associated immune‐dysregulation, and immunosuppressive treatment is thought to create favorable conditions for fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes Mellitus, neutropenia, lymphopenia, organ transplant and recently COVID-19 are the commonest predisposing factors in this type of infections [2] , [3] , [4] , [5] , [6] , [7] , [8] . Diabetes Meletus is a key factor of developing mucormycosis through three different hypotheses: 1- impaired neutrophil function, 2- decreased binding of transferrin to iron and 3- increased GRP-78.…”
Section: Introductionmentioning
confidence: 99%